Pengaruh Pertumbuhan Profitabilitas Dan Kebijakan Dividen Terhadap Harga Saham PT. Bank Central Asia Tbk Periode 2017-2021 - Octaviani, Reninda (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to analyze the effect of growth, profitability, and dividend policy on the share price of PT. Bank Central Asia Tbk in the 2017-2021 period. The type of data used is secondary data derived from the company's annual report. The sample of this study amounted to 30 samples using the purposive sampling method from 1 company that matched the criteria in 5 periods. Data analysis used using descriptive statistical analysis tests, classical assumption tests, multiple linear regression analysis tests, and hypothesis tests. The results of this study show that the T value of Profitability Growth has a positive and significant effect of 0.005 on the Share Price, the Dividend Policy has a positive and significant effect of 0.005 on the Stock Price. The result of the regression calculation is that the value of the coefficient of determination (R square) is 0.998 or 99.8%. This mean that the influence between the independent variable (X1) and (X2) on the dependent variable (Y) is 99.8%.